1995
DOI: 10.1128/mcb.15.4.2019
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Sequence Element-Binding Transcription Factor (PTF) Is a Multisubunit Complex Required for Transcription of both RNA Polymerase II- and RNA Polymerase III-Dependent Small Nuclear RNA Genes

Abstract: The proximal sequence element (PSE), found in both RNA polymerase II (Pol II)-and RNA Pol IIItranscribed small nuclear RNA (snRNA) genes, is specifically bound by the PSE-binding transcription factor (PTF). We have purified PTF to near homogeneity from HeLa cell extracts by using a combination of conventional and affinity chromatographic methods. Purified PTF is composed of four polypeptides with apparent molecular masses of 180, 55, 45, and 44 kDa. A combination of preparative electrophoretic mobility shift a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 44 publications
9
133
1
3
Order By: Relevance
“…However, whereas purified TDF completely restored transcription of the subclass 1 (5S RNA) and subclass 2 (tRNA and VA RNA) genes, it only partially restored transcription of subclass 3 (U6 and 7SK RNA) genes. The latter result suggests that additional subclass 3-specific factors also are partially inactivated by cycloheximide treatment and are consistent with previous demonstrations (for review, see Yoon et al 1995) of such factors. Nevertheless, these results indicate that TDF is a general transcription factor essential for transcription of all three subclasses of class III genes.…”
Section: Tdf Is An Essential Basal Factor That Is Broadly Required Fosupporting
confidence: 81%
“…However, whereas purified TDF completely restored transcription of the subclass 1 (5S RNA) and subclass 2 (tRNA and VA RNA) genes, it only partially restored transcription of subclass 3 (U6 and 7SK RNA) genes. The latter result suggests that additional subclass 3-specific factors also are partially inactivated by cycloheximide treatment and are consistent with previous demonstrations (for review, see Yoon et al 1995) of such factors. Nevertheless, these results indicate that TDF is a general transcription factor essential for transcription of all three subclasses of class III genes.…”
Section: Tdf Is An Essential Basal Factor That Is Broadly Required Fosupporting
confidence: 81%
“…Importantly, ChIP analyses showed that, in cells, p300 is targeted to actively transcribed tRNA genes, as well as to U6 RNA genes that do not contain binding sites for TFIIIC. It is possible, therefore, that promoter recognition factor SNAPc/PTF (42,54,73) or Oct-1 (55,59) is involved in recruiting p300 to the U6 gene.…”
Section: Discussionmentioning
confidence: 99%
“…At least four polypeptides with reported molecular masses of approximately 180-200, 50-55, 44-45 and 43-45 kDa have been identified as common components of SNAPc and PTF (Henry et al, 1995;Yoon et al, 1995). The TATA-box-binding protein (TBP), which is required for snRNA transcription by both RNAP 11 and RNAP I11 (Margottin et al, 1991 ; Lob0 et al., 1991;Simmen et al, 1991;Zamrod et al, 1993;Heard et al, 1993; Bernds et al, 1993;Sadowski et al, 1993), was considered to be an integral subunit of SNAPc (Sadowski et al, 1993;Henry et al, 1995), but was not detected at significant levels in purified PTF (Yoon et al, 1995;Yoon and Roeder, 1996). Except for this difference, PTF and SNAPc appear to be identical.…”
mentioning
confidence: 99%
“…Different research groups have termed it the PSE-binding protein (PBP), proximal transcription factor (PTF), or small nuclear RNA activator protein complex (SNAPc) (Waldschmidt et al, 1991;Murphy et al, 1992;Simmen et al, 1992;Sadowski et al, 1993). It is capable of activating U1 and U2 gene transcription by RNAP 11, as well as U6 and 7SK gene transcription by RNAP I11 (Sadowski et al, 1993;Henry et al, 1995;Yoon et al, 1995). At least four polypeptides with reported molecular masses of approximately 180-200, 50-55, 44-45 and 43-45 kDa have been identified as common components of SNAPc and PTF (Henry et al, 1995;Yoon et al, 1995).…”
mentioning
confidence: 99%